Population pharmacokinetics and toxicodynamics of continuously infused linezolid in critically ill patients - Wicha, Sebastian Georg; Mair, Andrea; Chiriac, Ute; Frey, Otto Roman; Fuchs, Thomas; Gaasch, Max; Hagel, Stefan; Richter, Daniel; Roberts, Jason A.; Röhr, Anka; Weigand, Markus A.; Brinkmann, Alexander (International journal of antimicrobial agents, 2022)
Objectives - Linezolid is a treatment option against multi-drug-resistant Gram-positive pathogens. Continuous infusion of linezolid has been proposed to optimize antimicrobial exposure, although pharmacokinetic data from large patient cohorts are lacking. - Methods - Population pharmacokinetics and the time-dependent association between linezolid exposure and the occurrence of thrombocytopenia in 120 critically ill patients were described. Monte Carlo simulations evaluated pharmacokinetic/pharmacodynamic/toxicodynamic target attainment in relation to body weight and creatinine clearance for continuously infused doses of 300-2400 mg/day. - Results - Linezolid pharmacokinetics were highly variable (interindividual variability of clearance: 52.8% coefficient of variation). Non-linear clearance was quantified, which decreased from 6.82 to 3.82 L/h within 3-6 days in the population. A relationship between linezolid exposure and platelet count over time was established. For standard dosing (1200 mg/day), the model predicted Grade 2, 3 or 4 thrombocytopenia (<75 × 103/µL, <50 × 103/µL and <25 × 103/µL) in 21.7%, 10.4% and 2.5% of patients at day 14, respectively. Patients with impaired renal function displayed higher risk. The overall probability of Grade 3 thrombocytopenia could be reduced from 10.4% using standard dosing to 6.3% if a linezolid steady state plasma concentration of 7 mg/L is targeted, suggesting a value of therapeutic drug monitoring (TDM). - Conclusion - Dosing linezolid by continuous infusion should include considerations of creatinine clearance and body weight to maximize the achievement of therapeutic exposures. However, due to the high variability in individual dose, optimization using TDM seems necessary to optimize linezolid dosing under continuous infusion to avoid toxicity, particularly if longer treatment courses are expected.
Gesehen am 28.06.2022